KEBIJAKAN PEMERINTAH DALAM MEMBANGUN KETENAGAKERJAAN YANG BERKELANJUTAN UNTUK MENSEJAHTERAKAN KEHIDUPAN MASYARAKAT - Junaheni Afifah; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Indonesia is facing quite complex employment problems. This contributes to the development of human resource competencies in Indonesia to be able to compete at the national, regional, and international levels. Government policy on sustainable employment is the main focus in creating an inclusive, sustainable, and future-oriented work environment. This paper aims to analyze the strategies and policies implemented by the government to improve sustainable employment development. The workforce in Indonesia still has various problems, such as high unemployment rates, low quality of workforce, wages, social security, and so on. This analysis also discusses challenges and opportunities in dealing with labor issues, this paper also implements the concept of competitiveness. Through this concept, it is found that efforts to increase competitiveness can start from the substance of the labor sector such as skills and infrastructure. Then, increasing competitiveness also requires reform of the employment system which is regulated in such a way by the government to obtain better quality human resources in the future.